Homogentisic acid induces cytoskeleton and extracellular matrix alteration in alkaptonuric cartilage. Issue 8 (20th January 2021) - Galderisi, Silvia; Cicaloni, Vittoria; Milella, Maria S.; Millucci, Lia; Geminiani, Michela; Salvini, Laura; Tinti, Laura; Tinti, Cristina; Vieira, Otilia V.; Alves, Liliana S.; Crevenna, Alvaro H.; Spiga, Ottavia; et al.
Abstract: Alkaptonuria (AKU) is an ultra‐rare disease caused by the deficient activity of homogentisate 1, 2‐dioxygenase enzyme, leading the accumulation of homogentisic acid (HGA) in connective tissues implicating the formation of a black pigmentation called "ochronosis." Although AKU is a multisystemic disease, the most affected tissue is the articular cartilage, which during the pathology appears to be highly damaged. In this study, a model of alkaptonuric chondrocytes and cartilage was realized to investigate the role of HGA in the alteration of the extracellular matrix (ECM). The AKU tissues lost its architecture composed of collagen, proteoglycans, and all the proteins that characterize the ECM. The cause of this alteration in AKU cartilage is attributed to a degeneration of the cytoskeletal network in chondrocytes caused by the accumulation of HGA. The three cytoskeletal proteins, actin, vimentin, and tubulin, were analyzed and a modification in their amount and disposition in AKU chondrocytes model was identified. Cytoskeleton is involved in many fundamental cellular processes; therefore, the aberration in this complex network is involved in the manifestation of AKU disease. Abstract : In chondrocyte cells, there is a close correlation and physical interconnection between cytoskeleton and extracellular matrix (ECM). Therefore, the alterations in the cytoskeletal structure lead to the impairment of the structure and the activity of ECM. In this study, the role of HGA metabolite accumulation in chondrocytes, which is responsible for the ultra‐rare disease alkaptonuria (AKU), was evaluated as inducer of structural alteration of cellular cytoskeleton and of the cartilage ECM, contributing to the manifestation of AKU pathology.